Malaysian biotechnology corporation Universiti Malaysia Pahang and Evolva collaborate to establish centre of excellence for Malaysian natural products (focus on biosynthesis of high value indigenous Malaysian natural product) - UMP, PNC (Penerbit UMP, 2014)

(untitled)
Reainch, Switzerland 4 June 2014 - Evolva Holding SA (SIX: EVE) announced that it will collaborate with Universiti Malaysia Pahang (UMP) to establish a scientific Centre of Excellcence for natural product from Malaysia as part of the Flavor and Fragrance Cluster in the state of Pahang.